Microvascular disease and heart failure with reduced and preserved ejection fraction in type 2 diabetes - Ify R. Mordi; Aaron Tee; Colin N. Palmer; Rory J. McCrimmon; Alexander S.F. Doney; Chim C. Lang (ESC Heart Failure, 2020)
Abstract Aims Identification of patients with type 2 diabetes (T2D) at increased risk of incident heart failure (HF) beyond traditional risk factors such as prior myocardial infarction (MI) might allow selection of patients who would benefit from preventative treatment. Microvascular disease (MiVD) is thought to play a pathophysiological role in the development of HF in T2D; however, its association with new‐onset HF with reduced or preserved ejection fraction has not been specifically defined. Methods and results Patients in the Genetics of Diabetes Audit and Research Tayside Scotland study were linked to echocardiography, prescriptions, and clinical outcomes. In total, 9141 patients with T2D were identified for analysis. Clinical variables and the presence of retinopathy, nephropathy, and neuropathy were assessed. Cumulative incidence was calculated for the association of both individual and the total number of MiVD states and incident HF. Median follow‐up was 9.3 years. In total, there were 900 HF events. The presence of any MiVD was independently associated with both HF with reduced ejection fraction (hazard ratio 1.40; 95% confidence interval 1.11–1.76, P = 0.004) and HF with preserved ejection fraction (hazard ratio 1.38; 95% confidence interval 1.10–1.72, P = 0.005), with a stepwise association between the number of MiVD states and risk of incident HF (P for trend <0.001). Similar associations were found in sensitivity analyses limited to patients without a prior MI, and using competing risks analysis. Conclusions Individuals with T2D and with MiVD are at risk of incident HF independent of a history of prior HF or MI. Patients with MiVD could benefit from screening for HF and individualized therapy with treatments that lower HF risk.